Terrenos e acrescidos de marinha: um estudo de caso do arqueoalagado do Piri, Belém-PA - SILVA, Jordana Maciel da (2018)
The flooded tonnage of Piri, Belém- Pa, inserted in the region considered by the Secretaria de Patrimônio da União as a sea area, has it “possession” questioned by the Prefeitura Municipal de Belém. Legal barriers leverage a series of questions, since the criteria to determine the basic topographic quota of the lands do not contemplate areas that have landfills. The legal indecision regarding “possession” causes damage to the residents of this region located on the seafront and “lowland” area in the 1stLégua Patrimonial of the city. Thus, this work investigated the criteria for defining land and marine resources used by the União in the regularization of urban plots on the Piri flooded tonnage, Belém-PA. For this, cartography of the area was carried out, application of questionings and reading of references about the theme. Technical and legal insecurities are perceived in various procedures adopted in the determination and maintenance of such land under the União protection. Uncertainties also permeate the population about wich taxes (IPTU and/or occupancy rate) and for whom (Município and/or União) must pay the taxes. It is the duty of the Município and the União to mobilize educational actions on the subject, pointing out the implications for the daily lives of residents in the area, so that efforts can be focused on better management of the space.